2006
DOI: 10.1002/app.23946
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of modified bismaleimide/polysulfone semi‐interpenetrating polymer networks

Abstract: The present work reports a new method of preparing semi‐interpenetrating polymer network (semi‐IPN) membranes through in situ polymerization of bismaleimide (BMI) within polysulfone (PSF). It was found that BMI could be polymerized at ambient conditions in the presence of a proton donor and PSF without the use of an initiator or a catalyst. Chemical structure characterization of these semi‐IPNs by Fourier transform infrared attenuated total reflection (FTIR‐ATR) revealed the possibility of imide cleavage and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…Absence of red or purple color in the case of isopropanol indicates that BMI probably underwent a free radical polymerization as reported elsewhere [24]. The chemical structures of modified BMI-PEI as well as modified BMI-PSF were analyzed by ATR-FTIR and XPS spectroscopy as found elsewhere [25,26].…”
Section: Resultsmentioning
confidence: 70%
“…Absence of red or purple color in the case of isopropanol indicates that BMI probably underwent a free radical polymerization as reported elsewhere [24]. The chemical structures of modified BMI-PEI as well as modified BMI-PSF were analyzed by ATR-FTIR and XPS spectroscopy as found elsewhere [25,26].…”
Section: Resultsmentioning
confidence: 70%
“…It was observed that BMI could be polymerized slowly inside and through PEI/NMP solutions at ambient conditions in the presence of ethyl alcohol [11][12][13]. The progress of polymerization was followed by measuring the viscosity, color change and spectroscopic analysis as discussed in details in our earlier work [11].…”
Section: Resultsmentioning
confidence: 99%
“…The mixed gas selectivity with 6 and 8% PEGDa is 43 ± 10 and 54 ± 9 respectively. In summary, all the formulations, with the exception of the PEGDa/PEI-4% membrane, match or slightly surpass the PEI dense film selectivity and significantly surpassing the dense film selectivity for PEGDa (20). There was no shortfall of the mixed gas selectivity in comparison to the pure gas values within experimental error, which indicated no plasticization.…”
Section: Co 2 /Ch 4 Transport Characteristicsmentioning
confidence: 70%
“…Our lab reported semi-IPN membranes having 15 times higher permeance than the parent polymers without a significant decrease in gas selectivity [20][21][22][23]. Recently we have reported the pure gas permeation studies based on semi-IPN membranes of commercially important glassy polymers and poly (ethylene glycol) diacrylate (PEGDa) [24,25].…”
Section: Introductionmentioning
confidence: 99%